Predicting the structural reliability of LNG processing plate-fin heat exchanger for energy conservation - Saggu, M.H. (MDPI AG, 2020)
Liquefied natural gas (LNG) is one of the hydrocarbon fuels with the least carbon footprint having a rapidly rising global share in the prime energy market. LNG processing for transportation at longer distances works under cryogenic conditions, especially when used for liquefaction and gasification applications. The supply chain of the eco-environmental friendly hydrocarbon is heavily dependent on the processing plant used for liquefaction and subsequent re-gasification of the natural gas. Plate-fin heat exchangers are extensively used in the LNG industry for both re-gasification as well as liquefaction processes. The exchange of heat during the process of natural gas phase change involves plate-fin heat exchangers working under cryogenic low-temperature conditions. The heat exchangers are designed to have brazed joints that are most vulnerable to failure under these temperature conditions. One failure of such a joint can not only hinder the supply chain but also may result in fire and life hazards. In almost all earlier studies, analytical and numerical methods were used to analyze these braze joints using finite element method methods and examining the stresses while keeping them at or near to ambient conditions. In this research, the plate-fin heat exchanger is investigated for its structural stability of brazed fins for three different fin configurations: plain, wavy and compound having different joint geometries. In addition, the analyses are carried out using experimentally measured brazed joint strength which is measured to be on average 22 lower than the base material strength owing to brazing process and resultant heat-affected zone (HAZ). Therefore, the reliability is assessed for these joints in terms of factor of safety (FOS) while keeping in view the actual yield criteria. It was found that the structural stability of compound fins configuration is weakest amongst all considered fin configurations. The failure of the compound fin brazed joint is expected to be along the horizontal path of the joint due to yielding. The study also predicts the life of the fin brazed joints in different joining directions with different topologies of fins commonly recommended in the literature. It is observed that the commonly recommended safe fin geometries are predicted to be susceptible to failure if a reduction in the brazed joint is considered. The analysis and recommendation in this paper shall provide a reliable and safe design approach for plate-fin exchangers for different operating conditions especially in low to cryogenic temperature applications. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.